Contribution of the drought tolerance‐related Stress‐responsive NAC1 transcription factor to resistance of barley to Ramularia leaf spot. (25th August 2014) - McGrann, Graham R. D.; Steed, Andrew; Burt, Christopher; Goddard, Rachel; Lachaux, Clea; Bansal, Anuradha; Corbitt, Margaret; Gorniak, Kalina; Nicholson, Paul; Brown, James K. M.
Summary NAC proteins are plant transcription factors that are involved in tolerance to abiotic and biotic stresses, as well as in many developmental processes. Stress‐responsive NAC1 (SNAC1) transcription factor is involved in drought tolerance in barley and rice, but has not been shown previously to have a role in disease resistance. Transgenic over‐expression of HvSNAC1 in barley cv. Golden Promise reduced the severity of Ramularia leaf spot (RLS), caused by the fungus Ramularia collo‐cygni, but had no effect on disease symptoms caused by Fusarium culmorum, Oculimacula yallundae (eyespot), Blumeria graminis f. sp. hordei (powdery mildew) or Magnaporthe oryzae (blast). The HvSNAC1 transcript was weakly induced in the RLS‐susceptible cv. Golden Promise during the latter stages of R. collo‐cygni symptom development when infected leaves were senescing. Potential mechanisms controlling HvSNAC1‐mediated resistance to RLS were investigated. Gene expression analysis revealed no difference in the constitutive levels of antioxidant transcripts in either of the over‐expression lines compared with cv. Golden Promise, nor was any difference in stomatal conductance or sensitivity to reactive oxygen species‐induced cell death observed. Over‐expression of HvSNAC1 delayed dark‐induced leaf senescence. It is proposed that mechanisms controlled by HvSNAC1 that are involved in tolerance to abiotic stress and that inhibit senescence also confer resistance to R. collo‐cygni and suppress RLS symptoms. This provides further evidence for an association between abiotic stress and senescence in barley and the development of RLS.